Quantity of Antioxidant on the Moroheiya Leaves (Corchorus capsularis Linn.) undergoing Hot-Air Drying Process - นาชัยสินธุ์ มะลิ; พิศดู สมภพ; เหลี่ยมสิงขร ศราวุธ; คำผุย กนกอร (Journal for Developing the Social and Community, 2016)
The purposes of this research were to study physical quality changes and antioxidant of Moroheiya leaves undergoing hot- air drying process. at drying temperature of 40, 60 and 80oC. and 6% d.b. of final moisture content of Moroheiya leaves. The physical qualities studied were moisture content, color, water activity and antioxidant. The results showed that effect of drying temperature on the moisture content of Moroheiya leaves dried was decreased rapidly at the 80oC. with Higher drying temperature causes the color tended to be lighter. Water activity and anti-oxidant of Moroheiya leaves were decreased undergoing higher drying temperature. The lowest drying temperature of the experiment (40oC) as compared with higher drying temperature showed minor changes in moisture content, color, water activity and antioxidant of Moroheiya leaves.